Pelvic Floor Muscle Training to Prevent Stress Urinary Incontinence in Pregnancy - Rubab Riaz, Fareesa Waqar, Saadia Sultana (Journal of Islamic International Medical College, 2017)
Objective: To check the frequency of stress urinary incontinence and to assess the awareness about pelvic floor muscle training for stress urinary incontinence among pregnant women. Study Design: Cross sectional observational study. Place and Duration of Study: The study was conducted from April 02, 2017 to July 30, 2017, at the department of Obstetrics and Gynecology Islamic International Medical College, Pakistan Railway Teaching Hospital,Rawalpindi. Materials and Methods: A total of 322 pregnant women between gestational ages of 12 to 38 weeks were selected by convenience sampling technique. A structured closed questionnaire was used for data collection.All data were analyzed in SPSS version 21 and percentages and mean were calculated. Results: The frequency of stress urinary incontinence among our study population was 32.9%. Awareness about pelvic floor muscle training was seen in only 9% of women in general and 27% of women suffering from stress urinary incontinence. Conclusion: Frequency of stress urinary incontinence in our pregnant population is high. Awareness about pelvic floor muscle training and its benefits is very scant and very few pregnant women suffering from stress urinary incontinence are doing pelvic floor muscle training. This highlights the need of improving antenatal care.